Electroporation of lignocellulosic biomass - Intansarah Sahira, Mohd Noor (2018)
Nowadays, fossil fuels are still the primary energy sources but it cannot hold for a lifetime. Therefore, to overcome this limitation, biofuel is considered as a sustainable solution.A number of methods have been developed for producing biodiesel but with traditional method its take more time and associated with usage of huge amount of toxic solvents. Therefore, our research aimed how to reduce time of lignocellulosic biomass cells breakdown, with less energy input and eco-friendly.This study discussed how to break the bonding of lignocellulosic biomass that make biofuel in a short time using high voltage.As the lignocellulosic biomass are abundant and sustainable feedstock for biofuel production, Azolla was used as source of biomass as it shows greater potential of growth rate. To do this, we used electroporation process. This study produced an electroporation device to deform the cellulosic structure of lignocellulosic biomass to release sugar. Electroporation circuit isfabricated to employed a high voltage for shorter time on lignocellulosicbiomass to disrupt bonding between cellulose, hemicellulose and lignin.A cylinder shape stainless steel with height of 5cm and arc length of 5.3cm is used as the electroporation plate. A voltage within range 1 kV to 4.9 kVhas been used throughout this process. Finally, the potential of biofuels as one of energy source cannot be overlooked from the result of the present research because they can contribute considerably to supply energy for future.